Exponential stabilization with practical convergence of nonautonomous infinite-dimensional evolution equations - Damak, Hanen; Hammami, Mohamed Ali (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 We consider the asymptotic behaviors of solutions of certain differential equations in Banach spaces. It is proved that, under certain conditions with a restriction imposed on the perturbation term, certain classes of nonautonomous infinite-dimensional evolution equations can be almost feedback stabilized. We use integral inequalities and Lyapunov techniques to approach this problem. Moreover, we suggest some classes of memoryless state linear and nonlinear feedback controllers. To demonstrate the validity of the main result, an example is provided.